2022
DOI: 10.17130/ijmeb.861974
|View full text |Cite
|
Sign up to set email alerts
|

Beş Faktör Ki̇şi̇li̇k Özelli̇kleri̇ İle Sosyal Gi̇ri̇şi̇mci̇li̇k Eği̇li̇mi̇ Arasindaki̇ İli̇şki̇: Üni̇versi̇te Öğrenci̇leri̇ Örneği̇

Abstract: Bazı girişimciler güçlü bir para kazanma arzusuyla bir girişimde bulunurken, diğerleri sağladıkları sosyal fayda ile motive olurlar. Sosyal girişimcilerin kişilik özellikleri diğer girişimcilerden farklıdır. Sosyal girişimciler, başarılı bir girişimcinin tüm yeteneklerine ve güçlü bir değişim arzusuna sahiptir. Kollektif faaliyetlerde sosyal faydayı en üst düzeye çıkarmak için çalışırlar. Güçlü bir sosyal adalet anlayışına sahiptirler. Sosyal girişimciler kendinden emin, enerjiktirler ve başkalarını girişimler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Individuals with this trait are more inclined to be involved in volunteering as they are preoccupied with the needs of others (Sahinidis et al, 2020). Agreeableness is particularly important in the context of social entrepreneurship, where compassionate individuals prioritize social ideals over economic ones and work to address societal problems through cooperation and the development of social values and corroborate between agreeableness and social entrepreneurship intention (Yusif & Kamil, 2015, Hsu & Wang, 2018, Ip et al, 2018, Hossian et al, 2021, Luc,2020Kumcu & Cetinel, 2022). In contradiction, Milanovic et al (2021) found a negative relationship between agreeableness and social entrepreneurial intention.…”
Section: Agreeableness and Social Entrepreneurial Intentionmentioning
confidence: 99%
“…Individuals with this trait are more inclined to be involved in volunteering as they are preoccupied with the needs of others (Sahinidis et al, 2020). Agreeableness is particularly important in the context of social entrepreneurship, where compassionate individuals prioritize social ideals over economic ones and work to address societal problems through cooperation and the development of social values and corroborate between agreeableness and social entrepreneurship intention (Yusif & Kamil, 2015, Hsu & Wang, 2018, Ip et al, 2018, Hossian et al, 2021, Luc,2020Kumcu & Cetinel, 2022). In contradiction, Milanovic et al (2021) found a negative relationship between agreeableness and social entrepreneurial intention.…”
Section: Agreeableness and Social Entrepreneurial Intentionmentioning
confidence: 99%